Firm Size as Determinants of Intellectual Capital Disclosure - Fitri Ella Fauziah; Murharsito Murharsito (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2021)
The objective of this research was to investigate the effect of size of firm, leverage, audit committee and business complexity on the disclosure of intellectual capital. The sample of this study was manufacturing firms in the basic industrial and chemical sub sectors that registered on the Indonesia Stock Exchange in the period of 2019. The sample was determined by using a method of purposive sampling, there were 104 samples. This research used multiple linear regression methods. Partly, the results of this analysis show that only firm size has an influence on intellectual capital disclosure. Meanwhile, the audit committee, business complexity and leverage have no significance on the disclosure of intellectual capital.